Emotional Regulation Ability on Test Results: Factors Affecting Motivation and Learning Achievement - Wardana, I Ketut; Natasya Dewi Nugraha, Luh Putu; Arsana, Anak Agung Putu (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2024)
The ability to regulate emotions in the acceptance of test results can impact both the increase and decrease of motivation. Unfortunately, there has not been much research explaining this phenomenon. Therefore, this study aimed to examine the influence of emotions on the acceptance of test results on students' learning motivation. This research used an ex post facto approach with a cause-and-effect correlation design. The population consisted of 300 students at SMPN 2 Kuta Selatan. Using purposive sampling, 30 students were involved as research samples. The research instrument consisted of 21 statements from the DAS questionnaire about test results, 20 statements about student motivation, and a formative test. Data were analyzed descriptively, using correlation statistics and paired sample t-tests. The research results showed that there was a significant relationship between the ability to manage depression, anxiety, and stress in the acceptance of test results. In addition, students with better emotional management skills tended to have positive motivation if their test results were disappointing. Meanwhile, students with low emotional abilities also had low motivation. For these affecting factors on students’ achievements, this study suggests a more holistic pedagogical approach and intervention as essential components in efforts to improve their learning achievement